INNOVATSION TEXNOLOGIYALARNI ISHLAB CHIQARISHGA JORIY ETISH - Kobilova , Go‘zal Ilxomovna; Mamatqulov , Bobirjon Ulug‘bek o‘g‘li (Educational Research in Universal Sciences, 2023)
This article is written on the basis of the project of innovative technology for the production of mint and lemon tea, in which the beneficial properties of lemon and mint for human health are studied and described in detail.